UNFAIR BUSINESS COMPETITION AGAINST TRADITIONAL RETAILERS DUE TO THE DOMINANCE OF THE MODERN RETAIL MARKET - Agus Armaini Ry; Herlina Hanum Harahap; Muhammad Ansori Lubis (Jurnal Ilmiah METADATA, 2026)
The market dominance of modern retail has created unequal competition for traditional retailers. Modern retailers possess substantial capital, extensive distribution networks, and efficient management systems, enabling them to sell goods at lower prices. Conversely, traditional traders purchase goods in small quantities, resulting in higher cost prices. Modern retailers offer shopping comfort through air conditioning, good lighting, neat product displays, cashless payment options, and adequate parking. These are key preferences for modern consumers. Many modern retailers are permitted to operate near traditional markets or residential areas, seizing market share that was previously the catchment area of ​​traditional traders.